SAESD – Sistema de Apoio para a Avaliação de cursos Superiores a Distância - Lachi, Ricardo Luís; Rocha, Heloísa Vieira da (Cadernos de Informática, 2011)
This article describes a computational system developed to collect and present relevant data to evaluation of a distance university course by Internet. The whole process of system development is presented, focused on the application of Alpha Cronbach’s coefficient, in order to demonstrating reliability of data considered relevant to being collected.